2016
DOI: 10.1136/postgradmedj-2016-134131
|View full text |Cite
|
Sign up to set email alerts
|

Running on empty: a review of nutrition and physicians' well-being

Abstract: Resident and physician burnout is a complex issue. Adequate nutrition and hydration play important roles in the maintenance of health and well-being of all individuals. Given the high prevalence of burnout in physicians, we believe that in addition to issues related to heavy workload, structure and length of shifts, the current status of physicians' nutrition and hydration and their effects on their work performance and well-being should also be addressed. In this review, we summarise the current evidence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 39 publications
2
20
0
3
Order By: Relevance
“…Además de disminuir el reporte de estrés y de síntomas depresivos, otorga múltiples beneficios sobre la salud física y el bienestar general del individuo. 34 Este estudio destaca por ser el primer trabajo que analiza el auto-reporte de burnout en traumatólogos que ejercen en Chile. Sin embargo, no se encuentra exento de limitaciones.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Además de disminuir el reporte de estrés y de síntomas depresivos, otorga múltiples beneficios sobre la salud física y el bienestar general del individuo. 34 Este estudio destaca por ser el primer trabajo que analiza el auto-reporte de burnout en traumatólogos que ejercen en Chile. Sin embargo, no se encuentra exento de limitaciones.…”
Section: Discussionunclassified
“…Pese a ese potencial sesgo, los resultados del presente estudio son, en su mayoría, comparables con la literatura internacional. 5,7,30,31,33,34 Finalmente, este reporte fue realizado sólo en especialistas en Ortopedia y Traumatología, por lo que no necesariamente refleja la realidad de otras especialidades. Sin embargo, existen reportes internacionales similares entre especialidades quirúrgicas 1,5,8,22,23 y en médicos en formación en Chile.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…There is a particular issue for staff who work out of hours such as nursing and junior doctors, and similar issues have been described in the US. 34 The case studies identified a lack of quality food provision for staff working out of hours with a high reliance on vending machines with items with long shelf life and preponderance of energy dense food and snacks and sugary drinks. There was a recognition that the provision of high-quality food environment for staff can increase staff and visitors eating in canteens/local food outlets and have a positive impact on staff wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…25 Proper nutrition and PA are important components of physician wellness. 26 Poor nutrition can affect HCPs' physical, emotional, and cognitive functioning 27 and improving physician nutrition is associated with enhanced cognitive testing results. 28 HCPs' regular PA correlates with their career satisfaction, improved sense of well-being, increased empathy, and decreased burnout.…”
Section: Introductionmentioning
confidence: 99%